William E. Chandler papers - Chandler, William E. (William Eaton), 1835-1917.
Principally bound volumes of correspondence documenting Chandler's work as assistant secretary of the treasury (1865-1867), secretary of the navy (1882-1885), U.S. senator from New Hampshire (1887-1901), and chairman of the Spanish Treaty Claims Commission (1901-1908). Includes material reflecting Chandler's prominence in the Republican Party and his role in the presidential campaigns of 1868, 1872, and 1880 and in the disputed election of 1876 between Rutherford B. Hayes and Samuel J. Tilden. Correspondents include Chester Alan Arthur, James Gillespie Blaine, Montgomery Blair, George S. Boutwell, Jay Cooke, Walter Quintin Gresham, William Pitt Kellogg, Philander C. Knox, William McKinley, William Orton, Orville Hitchcock Platt, Thomas Collier Platt, and Lew Wallace.
U.S. secretary of the navy, senator from New Hampshire, and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arthur, Chester Alan, -- 1829-1886 -- Correspondence; Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Blair, Montgomery, -- 1813-1883 -- Correspondence; Boutwell, George S. -- 1818-1905 -- Correspondence; Cooke, Jay, -- 1821-1905 -- Correspondence; Gresham, Walter Quintin, -- 1832-1895 -- Correspondence; Hayes, Rutherford Birchard, -- 1822-1893.; Kellogg, William Pitt, -- 1831-1918 -- Correspondence; Knox, Philander C. -- 1853-1921 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Orton, William, -- 1826-1878 -- Correspondence; Platt, Orville Hitchcock, -- 1827-1905 -- Correspondence; Platt, Thomas Collier, -- 1833-1910 -- Correspondence; Tilden, Samuel J. -- 1814-1886.; Wallace, Lew, -- 1827-1905 -- Correspondence; United States. -- Department of the Treasury -- Officials and employees; United States. -- Navy Department -- Officials and employees; United States. -- Spanish Treaty Claims Commission; Republican Party (U.S. : 1854- ); Contested elections -- United States; Presidents -- United States -- Election -- 1868.; Presidents -- United States -- Election -- 1872.; Presidents -- United States -- Election -- 1876.; Presidents -- United States -- Election -- 1880.; New Hampshire -- Politics and government -- 1865-1950.; United States -- Politics and government -- 1865-1933.; Cabinet officers; Lawyers; Senators, U.S. Congress -- New Hampshire